Quo Vadis Ormas Islam Moderat Indonesia? Meneropong Peran NU-Muhammadiyah di Era Revolusi Industri 4.0 (POLITEA, 2018)
This paper aims to discuss the practice of Islamic moderation which has been carried out by the two largest Islamic mass organizations in Indonesia, namely the Nahdlatul Ulama (NU) and Muhammadiyyah primarily in the era of the Industrial Revolution (RI) 4.0. This article is written with the library research method. This study is descriptive explorative which analyzes the challenges of Nahdlatul Ulama and Muhammadiyyah in the aspects of da'wah and social in the fourth industrial revolution era. The conclusions of this study are: 1) NU and Muhammadiyah consistently guard the Indonesian nation with the value of Islamic moderation, without colliding between Islam and the Indonesian State; 2) Era (RI) 4.0 which is also known as the era of disruption requires NU and Muhammadiyyah to take part in utilizing technology to respond to the progress of the times in today's society. 3) In answering the challenges in this era of disruption, the two Islamic organizations need to make strategic efforts to counter Islamic radicalism, especially in the digital world; Key Words: Moderation, Islam, Nahdlatul Ulama, Muhammadiyyah, Industrial Revolution 4.0.